Calendar. (Chronicle of Higher Education, 1980)
The article presents a calendar of events for 1980 related to higher education in the U.S. Regional meeting of the National Association of Educational Buyers will be held on September 23. A seminar titled "Wage and Salary Administration for Small Colleges" will be held on September 24 to 26. "Programming with Pascal" workshop by the Association for Educational Data Systems will be held on September 25 to 26.